2011
DOI: 10.1007/s10597-011-9459-9
|View full text |Cite
|
Sign up to set email alerts
|

Depression Care Management for Chinese Americans in Primary Care: A Feasibility Pilot Study

Abstract: Objective: Addiction or Substance Use Disorder (SUD) is a growing public health problem which affects the person, the whole family and society. The primary care physician is often the first point of contact in health care and can play a significant role in early detection and intervention. It is well established that early intervention is associated with better outcome, however in their formal medical training; primary care physicians receive no formal training on drug addiction management. In this pilot study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
1

Year Published

2012
2012
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 24 publications
0
20
0
1
Order By: Relevance
“…While most agree collaborative care is important and effective in patient management, the evidence is divided on the effectiveness of care management components for depression. This is highlighted in the study by Kwong et al [33] that showed no advantage of adding a care management component relative to enhanced physician care in depressive symptomology.…”
Section: Resultsmentioning
confidence: 99%
“…While most agree collaborative care is important and effective in patient management, the evidence is divided on the effectiveness of care management components for depression. This is highlighted in the study by Kwong et al [33] that showed no advantage of adding a care management component relative to enhanced physician care in depressive symptomology.…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies were located in traditional primary care practice settings (Angeles et al, 2013;Boult, Rassen, Rassen, Moore, & Robison, 2000;Farmer, Clark, Drewel, Swenson, & Ge, 2011;Fortinsky, Kulldorff, Kleppinger, & Kenyon-Pesce, 2009;Katon et al, 2001;Richardson et al, 2014;Roy-Byrne et al, 2010;Saitz et al, 2013;Sommers, Marton, Barbaccia, & Randolph, 2000). Six studies were located in public-health community clinics (Béland et al, 2006;Counsell et al, 2007;Ell et al, 2010;Kwong, Chung, Cheal, Chou, & Chen, 2013;Roy-Byrne et al, 2014;Safren, O'Cleirigh, Skeer, Elsesser, & Mayer, 2013), and four studies were located in academic health care systems (Counsell et al, 2007;Huffman et al, 2014;Ross, Roberts, Campbell, Solomon, & Brouhard, 2004). The remaining studies were conducted in assisted-living settings (Bellantonio et al, 2008;Boult et al, 2001), a detoxification unit (Samet et al, 2003), Veterans Administration medical centers (Engelhardt, Toseland, Gao, & Banks, 2006), a community hospital (Leung et al, 2004), and OB/GYN clinics (Grote et al, 2015;.…”
Section: Included Studies and Participant Characteristicsmentioning
confidence: 99%
“…Across all 26 studies, most participants were White; however, five studies did not report the race/ethnicity of participants (Angeles et al, 2013;Béland et al, 2006;Bellantonio et al, 2008;Leung et al, 2004;. Two studies focused exclusively on Hispanic patients (Ell et al, , 2010, and one focused exclusively on Chinese American patients (Kwong et al, 2013).…”
Section: Included Studies and Participant Characteristicsmentioning
confidence: 99%
“…[ 40 ] . Gleichzeitig erscheint es immer notwendiger, besondere Versichertengruppen wie Patienten mit Migrationshintergrund, die entweder einen eingeschränkten Zugang zu medizinischen Dienstleistungen haben oder nicht ausreichend über das medizinische Versorgungs-und soziale Sicherungssystem informiert sind, individuell zu betreuen [ 41 ] . Aufgrund des neuen Ansatzes der Einzelfallbetreuung wäre hierbei jedoch zunächst zu überprüfen, welche Versichertengruppen besonders vom Fallmanagement profi tieren könnten bzw.…”
unclassified